Beyond Scarcity : Water Security in the Middle East and North Africa - World Bank (Washington, DC: World Bank, 2017)
Water has always been a source of risks and opportunities in the Middle East and North Africa. Yet rapidly changing socioeconomic, political, and environmental conditions make water security a different, and more urgent, challenge than ever before.